Effects of Organic tea concentration and application methods on growth and yield of Greenhouse Cucumber (Cucumis sativum L.) in Owo, South-western Nigeria - aderibigbe, adesunlola taye benjamin; Adu, Sunday; Obabire, Sadiq Ola (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Organic tea (mixture of Organic Manure Extract and Spent Bleaching Extract) is used as nutrient complements in agriculture and horticulture to increase plant growth and yield. In this study a 2 X 4 factorial experiment used CRD (Completely Randomized Design) to examined the effect of compost tea herein referred to as OT [organic tea (extract made from SBE and composted manure extract (OM)] as bio-stimulants at four different concentrations (0, 20, 30, and 40 %) on the growth and fruit yield in cucumber (Cucumis sativum L.) under greenhouse condition using foliar (FO) and drip irrigation (DR) application methods. Vegetative parameters (vine length, number of branches, number of leaf per plant, leaf area, and stem girth) were studied at 50% flowering stage and yield parameters (Date to flower initiation, No of male flower, No of female flower, male/female flower ratio, number of fruit/plant, fruit length, fruit diameter, fruit weight/plant) and yield / hectare, at harvest. From the experiment organic tea application via folia method exhibited enhanced vegetative growth while application via drip irrigation was found to be more effective in influencing the yield parameters significantly. Plants that received 20% OT showed variability, but were not significantly different from control plants (0%). Similarly, plants treated with 40% OT extract showed enhanced vegetative growth and fruit yield with good quality, but high diseases infection. This study therefore provides important information on the utilization of OT and application method for increased cucumber production in the study area.